2013
DOI: 10.1093/beheco/art079
|View full text |Cite
|
Sign up to set email alerts
|

The role of beginner's luck in learning to prefer risky patches by socially foraging house sparrows

Abstract: Although there has been extensive research on the evolution of individual decision making under risk (when facing variable outcomes), little is known on how the evolution of such decision-making mechanisms has been shaped by social learning and exploitation. We presented socially foraging house sparrows with a choice between scattered feeding wells in which millet seeds were hidden under 2 types of colored sand: green sand offering ~80 seeds with a probability of 0.1 (high risk-high reward) and yellow sand off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 52 publications
2
14
0
Order By: Relevance
“…Most published accounts of individual use of tactics are compatible with our model's expectation (Barnard & Sibly, 1981;Beauchamp, 2001;Bicca-Marques & Garber, 2005;Coolen, 2002;Coolen et al, 2001;Giraldeau, Hogan, & Clinchy, 1990;Ha & Ha, 2003;Ilan, Katsnelson, Motro, Feldman, & Lotem, 2013;Koops & Giraldeau, 1996;Mathot & Giraldeau, 2008;M onus & Barta, 2008;Morand-Ferron, Varennes, et al, 2011;Morand-Ferron, Wu, et al, 2011). In a series of experiments with house sparrows, Barnard and Sibly (1981) reported that producers obtained 19.8e38.3% of their food by joining and that scroungers obtained 38.5e48.8% of their food by searching.…”
Section: Discussionsupporting
confidence: 78%
“…Most published accounts of individual use of tactics are compatible with our model's expectation (Barnard & Sibly, 1981;Beauchamp, 2001;Bicca-Marques & Garber, 2005;Coolen, 2002;Coolen et al, 2001;Giraldeau, Hogan, & Clinchy, 1990;Ha & Ha, 2003;Ilan, Katsnelson, Motro, Feldman, & Lotem, 2013;Koops & Giraldeau, 1996;Mathot & Giraldeau, 2008;M onus & Barta, 2008;Morand-Ferron, Varennes, et al, 2011;Morand-Ferron, Wu, et al, 2011). In a series of experiments with house sparrows, Barnard and Sibly (1981) reported that producers obtained 19.8e38.3% of their food by joining and that scroungers obtained 38.5e48.8% of their food by searching.…”
Section: Discussionsupporting
confidence: 78%
“…Some aggressive or dominant individuals could for example be perceived as a stressor for their group-mates, thus increasing alert time and neophobia in difficult situations [ 23 , 24 ], while other conspecifics could have the very opposite effect, decreasing neophobia and alert time [ 13 ]. This underlines a system of conspecific recognition and flexibility in behavioural responses that may be affected by differences in behavioural traits and experiences [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, even if learning is not transmitted socially, variable task‐dependent learning abilities in a group can generate a skill pool effect (Giraldeau ) that allows social foragers to exploit a greater variety of food resources by simply joining each other's food findings (Giraldeau & Lefebvre ; Ilan et al. ). Thus, by providing the first evidence for task‐dependent differences in learning abilities of new tasks between dominants and subordinates in a cooperative bird, our study also suggests an interesting cascading effect: different social ranks that display different cognitive strategies can increase the variety of skills that may be generated in the group, which may then contribute to the benefits of group‐living.…”
Section: Discussionmentioning
confidence: 99%